2012
DOI: 10.1002/j.1875-9114.2012.01116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Pharmacist‐Led Warfarin Self‐Management Program on Quality of Life and Anticoagulation Control: A Randomized Trial

Abstract: A self-management warfarin program led by pharmacists resulted in significant improvement in the quality of life of patients receiving warfarin therapy as well as a reduction in the time required for anticoagulation monitoring, while maintaining a level of anticoagulation control similar to a high-quality specialized anticoagulation clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
125
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(142 citation statements)
references
References 23 publications
7
125
1
9
Order By: Relevance
“…55,57,[61][62][63][64][65] In 11 trials, the randomisation process proved to be adequate but no information was provided on the way in which participants were allocated to the study interventions. 58,60,[66][67][68][69][70][71][72][73][74] One trial 75 reported adequate details about the generation of the random sequence but failed to conceal the allocation of participants to study interventions. In contrast, another trial 76 reported adequate information on allocation concealment but failed to provide details on the randomisation process.…”
Section: Selection Biasmentioning
confidence: 99%
See 4 more Smart Citations
“…55,57,[61][62][63][64][65] In 11 trials, the randomisation process proved to be adequate but no information was provided on the way in which participants were allocated to the study interventions. 58,60,[66][67][68][69][70][71][72][73][74] One trial 75 reported adequate details about the generation of the random sequence but failed to conceal the allocation of participants to study interventions. In contrast, another trial 76 reported adequate information on allocation concealment but failed to provide details on the randomisation process.…”
Section: Selection Biasmentioning
confidence: 99%
“…Six of them had limited missing data with similar reasons for discontinuation across intervention groups. 59,69,72,74,76,79 Seven trials relied on an intention-to-treat approach and all dropouts were fully accounted for in the statistical analyses, 55,61,[63][64][65]71,75 while the other four reported no missing data. 58,60,62,78 Eight of the 26 included trials were at high risk of attrition bias, with more than 5% dropout rate and with missing data not appropriately tackled.…”
Section: Selection Biasmentioning
confidence: 99%
See 3 more Smart Citations